Improving the Еfficiency of Сash Flow Distribution Within the Social Insurance System - G. L. Podvoysky; A. V. Larionov (Мир новой экономики)
The presented research reveals the main directions of development of the social insurance system in Russia. The relevance of the study is caused by the modern challenges that have arisen in connection with the COVID‑19 pandemic, demonstrating the crucial role of social programs in ensuring the sustainability of countries. The subject of the research is the main factors affecting the development of the social insurance system. International experience shows that the development of private social insurance is a promising direction for the development of social insurance. The research reveals the main structural elements that should be formulated in the strategy for the development of the social insurance system in Russia.